2017
DOI: 10.1111/nyas.13311
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genetics of host shifts in herbivorous insects: insights from the age of genomics

Abstract: Adaptation to different host taxa is a key driver of insect diversification. Herbivorous insects are classic models for ecological and evolutionary research, but it is recent advances in sequencing, statistics, and molecular technologies that have cleared the way for investigations into the proximate genetic mechanisms underlying host shifts. In this review, we discuss how genome-scale data are revealing-at resolutions previously unimaginable-the genetic architecture of host-use traits, the causal loci underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 266 publications
0
40
0
Order By: Relevance
“…Beyond host use in herbivorous insects, a limited number of studies have tried to predict genome‐wide patterns of genetic differentiation in nature from laboratory or field experiments, and mostly, these have involved predicting genetic differentiation from QTL studies. The outlier loci underlying highest genetic differentiation between Drosophila yakuba mainland (Cameroon and Kenya) and Mayotte populations show concordance with Drosophila sechellia noni‐tolerance (performance) QTL (four of nine tolerance QTL, expected = 0.125, p = .013), but there is no overlap for D. sechellia preference QTL (expected = 0.35, p = .37), suggesting that noni‐performance is more predictable than noni‐preference (Vertacnik & Linnen, ; Yassin et al., ). Similarly, QTL for ecologically relevant traits colocalized with possible genetic regions affected by selection (as identified in genome scans) more than expected by chance in comparison with lake whitefish ecotypes (Rogers & Bernatchez, ).…”
Section: Discussionmentioning
confidence: 98%
“…Beyond host use in herbivorous insects, a limited number of studies have tried to predict genome‐wide patterns of genetic differentiation in nature from laboratory or field experiments, and mostly, these have involved predicting genetic differentiation from QTL studies. The outlier loci underlying highest genetic differentiation between Drosophila yakuba mainland (Cameroon and Kenya) and Mayotte populations show concordance with Drosophila sechellia noni‐tolerance (performance) QTL (four of nine tolerance QTL, expected = 0.125, p = .013), but there is no overlap for D. sechellia preference QTL (expected = 0.35, p = .37), suggesting that noni‐performance is more predictable than noni‐preference (Vertacnik & Linnen, ; Yassin et al., ). Similarly, QTL for ecologically relevant traits colocalized with possible genetic regions affected by selection (as identified in genome scans) more than expected by chance in comparison with lake whitefish ecotypes (Rogers & Bernatchez, ).…”
Section: Discussionmentioning
confidence: 98%
“…Beyond host-use in herbivorous insects, a limited number of studies have tried to predict genome-wide patterns of genetic differentiation in nature from lab or field experiments, and mostly these have involved predicting genetic differentiation from QTL studies. The outlier loci underlying highest genetic differentiation between Drosophila yakuba mainland (Cameroon and Kenya) and Mayotte populations, show concordance with Drosophila sechellia noni-tolerance (performance) QTLs (four of nine tolerance QTL, expected = 0.125, P = 0.013) but there is no overlap for D. sechellia preference QTLs (expected = 0.35, P = 0.37), suggesting that noni-performance is more predictable than noni preference (Yassin et al, 2016; Vertacnik & Linnen, 2017). Similarly, QTL for ecologically relevant traits co-localized with possible genetic regions affected by selection (as identified in genome scans) more than expected by chance in comparisons of lake whitefish ecotypes (Rogers & Bernatchez, 2007).…”
Section: Discussionmentioning
confidence: 78%
“…Considering that even species breeding on decaying and thus undefended tissues show this pattern, it is unlikely that coevolution and adaptation to plant defenses is a universal source of divergent selection and a necessary condition to explain insect diversification. A recent review found that most studies on candidate genes for host adaptation in phytophagous insects focus on resistance or detoxification of plant secondary metabolites [82], but the actual source of selection might be in other aspects of host use. Divergence following host shifts is pervasive in phytophagous insects and their parasitoids [26], despite the large variation in interaction outcomes.…”
Section: Interactions Do Not Predict Patterns Of Isolationmentioning
confidence: 99%